Influencing Factors of Migrants' Mental Health: A Case Study of Guangzhou and Shenzhen - Liu Wei; Luo Ziwen; Ouyang Zhen; Yang Senbin; Pan Yongen; Chen Shiqi; Wu Rong (Redai dili, 2022)
With the acceleration of urbanization and promotion of the integrated strategy of the Greater Bay Area (GBA), the number of migrants in the Pearl River Delta (PRD) has increased dramatically. With "Healthy China 2030" presented, mental health of migrants is of great significant to China's New-type Urbanization. Additionally, with the profound reforms in society and economy, the measurement and action mechanism of migrants' mental health deserve in-depth exploration. Using the data collected from the China Labor-force Dynamics Survey (CLDS) in 2016 for Guangzhou and Shenzhen and using the linear regression model, the study explored the effects of working environment, social interaction, and physical health on migrants' mental health. The second focus of this study was on the difference between migrants' mental health in Guangzhou and Shenzhen City through the empirical statistical results. Our empirical findings suggest that: 1) Migrants' mental health is significantly affected by working environment, social interaction, and physical health; among them, work satisfaction, lower work stress, community confidence, and self-rated health all have a positive impact on the mental health of migrants. Additionally, higher income is commonly associated with mental health. 2) For Guangzhou City, work stress, community confidence, self-rated health, drinking, exercise, and treatment have distinct impacts on the mental health of migrants. 3) For Shenzhen City, only work satisfaction, work stress, self-rated health, and treatment have distinct impacts on the mental health of migrants. In summary, this study used CLDS data from 609 migrants in 2016 to provide a more comprehensive picture of their working environment, social interaction, physical health, and mental health. Moreover, this study is a comparative analysis of migrants' mental health between Guangzhou and Shenzhen, which indicates that migrants' mental health in Guangzhou is mainly affected by work environment, social interaction, and physiological health; however, the work environment and physiological health play a significant role in migrants' mental health in Shenzhen. Based on the empirical findings, we call for further policymakers and practitioners to focus on both spatiality and heterogeneity in planning and governance. Municipal governments should consider the rationalization of land use and functional transformation to create harmonious social networks and promote migrants to better integrate into urban society. In addition, Guangzhou should increase and optimize leisure facilities and green space to strengthen the social interaction between migrants and locals, while it is of great importance to improve the working environment in Shenzhen and take measures to reduce migrants' working pressure by enhancing the safety and comfort of the working environment.